Study on reliability of punching shear of flat slabs without shear reinforcement according to NBR6118 - CARVALHO,M. L. (2017)
Abstract The frequent use of flat slabs in building constructions highlights the importance of improving the study of slab-column joints, particularly regarding the verification of the ultimate limit state of punching shear, given the complexity of this phenomenon. This article applies concepts of the Theory of Reliability in order to evaluate the safety of the formulation established by NBR6118: 2014 standard to check punching shear in flat slabs with centered columns. Twelve probabilistic model analysis for C and C' equations were developed, considering the influence that the variation of the slab thickness, the and the shear force eccentricity have on reliability index and failure rate . Results indicated that formulation of C boundary is reasonably safe, although C'boundary revealed index below expectations.